1993
DOI: 10.1046/j.1365-313x.1993.04010207.x
|View full text |Cite
|
Sign up to set email alerts
|

Oligogalacturonides inhibit the formation of roots on tobacco explants

Abstract: α-1,4-Oligogalacturonides with degrees of polymerization (DPs) ranging from 6 to 18 or 2 to 8 were added to tobacco leaf explants and root formation was evaluated after 15 days of incubation. Auxin-induced formation of roots was inhibited by oligogalacturonides with DPs 6–18 but not by the oligogalacturonides with DPs 2–8. The inhibition of root formation by the larger oligogalacturonides was prevented by increasing the amount of auxin present in the medium. Oligogalacturonides (DPs 6–18) also inhibited root f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
72
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 0 publications
4
72
0
Order By: Relevance
“…Furthermore, auxin-dependent responses are impaired in tobacco PG plants, and our previous work has shown that OGs suppress different responses regulated by auxin in tobacco (Bellincampi et al, 1993(Bellincampi et al, , 1996Mauro et al, 2002). In particular, tobacco PG plants show reduced sensitivity to IAA in experiments of rhizogenesis in leaf explants and inhibition of primary root growth.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Furthermore, auxin-dependent responses are impaired in tobacco PG plants, and our previous work has shown that OGs suppress different responses regulated by auxin in tobacco (Bellincampi et al, 1993(Bellincampi et al, , 1996Mauro et al, 2002). In particular, tobacco PG plants show reduced sensitivity to IAA in experiments of rhizogenesis in leaf explants and inhibition of primary root growth.…”
Section: Discussionmentioning
confidence: 95%
“…Because OGs have auxin-antagonistic activity and treatment with OGs leads to a decreased sensitivity to auxin in tobacco plants (Branca et al, 1988;Bellincampi et al, 1993Bellincampi et al, , 1996Altamura et al, 1998;Mauro et al, 2002), a support for the possible involvement of OGs in the phenotype of PG plants might be provided by the ability of auxin to revert some of the phenotypic features as well as by a decreased sensitivity to auxin of the PG plants.…”
Section: Increased Resistance Of Tobacco Pg Plants Is Abolished By Auxinmentioning
confidence: 99%
See 1 more Smart Citation
“…Meristem formation is triggered by a 10 3 -to 10 4 -fold increase in sensitivity to auxin of plant cells (Spanò et al, 1988;Maurel et al, 1991), possibly due to the tyrosine phosphatase activity of the RolB protein (Filippini et al, 1996), which may perturb the auxin signal transduction pathway. Oligogalacturonides, a class of oligosaccharins with antiauxin effects (Darvill et al, 1992;Bellincampi et al, 1993), inhibit auxin induction of rolB (Bellincampi et al, 1996).…”
Section: Ntbbf1 and Rolb Auxin Inductionmentioning
confidence: 99%
“…For example, flg22 and OGs generate an extracellular oxidative burst mediated by RESPIRATORY BURST OXIDASE HOMOLOG D (RbohD) and induce protection against the necrotrophic fungus Botrytis cinerea independently of the ethylene, jasmonic acid, and salicylic acid pathways and of the RbohD-mediated production of reactive oxygen species (ROS; Zhang et al, 2007;Galletti et al, 2008). The inhibition of auxin responses is another feature shared by PAMPs and DAMPs (Savatin et al, 2011); in the case of OGs, the inhibition of auxin responses has been described as a true antagonism (Branca et al, 1988;Bellincampi et al, 1993;Savatin et al, 2011). On the other hand, microarray analyses indicate that late responses to the two classes of elicitors are considerably different .…”
mentioning
confidence: 99%